Alignment of slender fibers and thin disks induced by coherent structures of wall turbulence. (December 2021) - Cui, Zhiwen; Huang, Wei-Xi; Xu, Chun-Xiao; Andersson, Helge I.; Zhao, Lihao
Abstract: The angular dynamics of small rigid fibers and disks in turbulent channel flow has been investigated numerically, focusing on interactions between particles and near-wall coherent vortices. Three distinctly different alignment patterns of fibers and disks around ensemble-averaged vortices were identified. From the wall to the channel center we observed a shear-dominant, a structure-dominant, and an isotropic region, each with its unique alignment pattern. These regions are different from those based on the conventional Reynolds-averaging view. The structure-dominant region, for instance, extends from about 3 to 60 wall units from the channel wall. Unlike the prevailing view that preferential alignment of fibers and disks are more common in the viscous sublayer than in the buffer layer, where the turbulence intensity reaches its maximum, the conditional ensemble-averaged approach revealed that fibers and disks align preferentially in the structure-dominant region. The particles moreover align differently in sweep and ejection events. The physical alignment mechanism we proposed may also be carried over to polymer- and fiber-induced drag reduction in wall-turbulence. Highlights: Alignment of fibers and disks around ensemble-averaged vortices in near-wall turbulence is investigated. Preferentially alignment is observed around the ensemble-averaged structures. The alignment mechanism in near-wall turbulence is discussed.